Leadership Patterns in Improving the Quality of State Civil Apparatus (ASN) Training in the Human Resources Development Agency (BPSDM) of Riau Islands Province - Riska Destiana; Donie Tuah Fitriano Putra (Kemudi, 2022)
Training is one of the competency development pathways for the State Civil Apparatus. To realize the implementation of quality, quality and standardized training for State Civil Apparatus in a sustainable manner, Human Resources Development Agency of Riau Islands Province implements training quality assurance through accreditation of training institutions. One of the elements assessment is the role of leaders in improving the quality of training through their contribution to building a quality culture, improving quality and building a positive work culture to improve performance. This study aims to analyze the role of the leader of the Human Resources Development Agency of Riau Islands Province in building a quality culture in the organization. The research method used is a mixed method (mix-method). The results showed that in most indicators of the assessment of the leader's role, respondents gave a very good assessment of the role of the leader Human Resources Development Agency of Riau Islands Province in building a quality culture. Leadership in the Human Resources Development Agency of Riau Islands Province is considered capable of being the main key to realizing the best quality of performance produced by the organization. The efforts of the Head of the Human Resources Development Agency of Riau Islands Province to create collaboration and coordination in achieving performance must continue to have the support and involvement of all employees.